Sistem Pengukur PH Air Untuk Tanaman Hidroponik - Nofriadi, Nofriadi; Dahriansyah, Dahriansyah; Lubus, Adi Prijuna (Arcitech: Journal of Computer Science and Artificial Intelligence, 2022)
Utilization of hydroponics for vegetable production, is a solution to produce commodities that are free of pesticide residues. harmful, But obstacles that are often experienced by cultivators that is the measuring instrument is not working properly. limited time to check the condition of the plant. plant leaves that do not grow normally, reduced ability of plant roots to absorb water and nutrient ions, and the withering of the plants caused by the unavailability of water to be absorbed by the roots. The purpose of this research is make the tool able to control the PH of water. The method used is the waterfall method